Composition and diversity of drift gillnet catches landed at PPI Cikidang Pangandaran - Gilar Budi Pratama; Khoerunnisa Nurani (Politeknik Negeri Sambas, 2025)
Cikidang Fishing Port is one of the fishing ports that plays an important role in capture fisheries in Pangandaran, with drift gillnet as the main fishing gear. The high use of this tool encourages the analysis of the diversity and composition of the catch to assess fishery productivity and maintain resource sustainability. This study aimed to analyze the composition and diversity of drift gillnet catches landed at the PPI Cikidang Pangandaran. The methods used include the calculation of production amount and value, Catch Per Unit Effort, percentage of catch composition, and diversity index. The data analyzed were obtained from the Cikidang PPI statistical report during the 2019-2021 period. The results showed that white pomfret (Pampus argenteus) was the most dominant species in the catch, with an average contribution of 26.4% per year, whereas yellow mackerel (Selaroides leptolepis) had the least catch (only 0.62% per year). The catch diversity index showed a value of 2.77 in 2019, 2.19 in 2020, and 2.21 in 2021, which falls into the medium category. Habitat conservation efforts and increased awareness of fishermen are also needed so that fishery resources in the Cikidang Fishing Port remain sustainable and productive in the long term.